Effectiveness of the golimumab educational program in ensuring healthcare professionals' awareness of risks described in the European risk management plan - Lauren Felo; Marijo Otero-Lobato; Anja Geldhof; Wim Noël (SAGE Publishing, 2019)
Background: The golimumab safety awareness study commenced in 2010 to measure, periodically, the awareness of golimumab prescriber healthcare professionals (HCPs) of specific risks associated with golimumab as well as awareness of the requirement to provide a patient alert card to each patient treated with golimumab, as described in the European golimumab educational program. The aim of this study was to measure the awareness of HCPs who prescribe or who intend to prescribe SIMPONI ® (golimumab) of the risks potentially related to golimumab and of the requirements for distributing the patient alert card, as described in the golimumab educational program. Methods: A structured, quantitative Web-based survey was conducted in 2010, 2012, 2014, and 2016 in eight European countries among HCPs who were at that time current or future prescribers of golimumab for patients with rheumatoid arthritis, psoriatic arthritis, ankylosing spondylitis, nonradiographic axial spondyloarthritis, or ulcerative colitis. Results: The overall golimumab risk awareness was high for golimumab prescriber HCPs across the risk statement categories (median awareness in 2016 across categories: 91%). The awareness of the golimumab risks was generally slightly higher among rheumatologists (75-98%) and gastroenterologists (73-97%) than among dermatologists (67-94%). Overall, the awareness of the requirements for handing out the patient alert card to golimumab-treated patients remained steady or increased slightly in 2016 relative to the other surveys. Conclusions: The results of this study show that the awareness of risks associated with golimumab by golimumab prescriber HCPs is high. The information made available to golimumab prescriber HCPs appears to have been sufficient with respect to golimumab risk awareness education.